Diagnosis And Efforts to Overcome Student Learning Difficulties During - Yendri, Yendri; Tanamir, Momon Dt. (Turast: Jurnal Penelitian dan Pengabdian, 2024)
Difficulty understanding learning materials, laziness, being easily discouraged, and being indifferent in learning are part of students' learning difficulties. These problems tend not all students can solve them alone. The teacher must play a role in helping solve the problems faced by these students, by making a diagnosis to find out where the learning difficulties faced by students are and find solutions. If the student's learning difficulties are left unchecked, the learning objectives will not be achieved properly. Student learning difficulties must be known and can be overcome as early as possible so that instructional learning can be achieved properly. To carry out the activity of diagnosing learning difficulties, it is carried out through several stages of activities such as; 1) students who are estimated to have learning difficulties, 2) localize learning difficulties, 3) determine the factors that cause learning difficulties, 4) estimate alternative assistance, 5) determine how to overcome them, and 6) follow-up. The diagnosis of learning difficulties is carried out using test and non-test techniques. The techniques used by teachers to diagnose learning difficulties include prerequisite tests (knowledge prerequisites, skills prerequisites), diagnostic tests, interviews, and observations. It was found that several students had learning difficulties in several subjects. The factors that cause these students to experience learning problems do not only come from the students themselves but also come from factors outside of the students such as family factors and factors from the school environment.